IMPROVING STUDENTS’ MOTIVATION AND LEARNING OUTCOMES ON TRIGONOMETRY THROUGH INTERACTIVE LEARNING MEDIA - Saepuloh Saepuloh; Rudi Priyadi; Supratman Supratman (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Mathematics is a subject that is always taught at every level of education. However, many students still think mathematics is complex and boring. The problem that arises is that it is difficult for students to understand the concept of trigonometry, so 60% of student learning outcomes are still below the KKM. This is due to the lack of student motivation in learning mathematics. Teachers must create creative and fun learning innovations based on these problems using interactive learning media. This study aims to develop interactive learning media that are feasible, practical, and effective. The type of research carried out is research and development with a 4D model by Thiagarajan. It consists of define, design, develop, and disseminate. The research was conducted at MA Assa'adah Jamanis. Data collection techniques are observation, interviews, questionnaires, and tests. The data analysis technique used is the analysis of validity, practicality, and effectiveness. The results of the learning media research developed are very feasible based on the validators of material experts and media experts and practical according to student questionnaires. The value of tcount is greater than ttable (20,494 > 2,131). This shows a significant average difference between the pre-test and post-test, which means the interactive media developed effectively improves mathematics learning outcomes. Based on student questionnaires, aspects of providing assistance and learning motivation obtained 83% or excellent results. Matematika merupakan mata pelajaran yang selalu diajarkan pada setiap jenjang pendidikan. Namun, banyak siswa masih menganggap matematika adalah hal yang kompleks dan membosankan. Masalah yang muncul adalah siswa sulit memahami konsep trigonometri, sehingga hasil belajar siswa 60% masih di bawah KKM. Hal ini akibat kurangnya motivasi siswa dalam belajar matematika. Berdasarkan permasalahan tersebut, guru harus menciptakan inovasi pembelajaran yang kreatif dan menyenangkan dengan menggunakan media pembelajaran interaktif. Penelitian ini bertujuan untuk mengembangkan media pembelajaran interaktif yang memenuhi kriteria layak, praktis dan efektif. Jenis penelitian yang dilaksanakan adalah penelitian dan pengembangan dengan model 4D oleh Thiagarajan. Terdiri dari define, design, develop, dan disseminate. Penelitian dilakukan di MA Assa'adah Jamanis. Teknik pengumpulan data adalah observasi, wawancara, angket, dan tes. Teknik analisis data yang digunakan adalah analisis validitas dan kepraktisan serta keefektifan. Hasil penelitian media pembelajaran yang dikembangkan sangat layak berdasarkan validator ahli materi dan ahli media, serta praktis menurut angket siswa. Nilai thitung lebih besar dari ttabel (20,494 > 2,131). Hal ini menunjukkan perbedaan rata-rata yang signifikan antara pre-test dan post-test, yang berarti media interaktif yang dikembangkan efektif dalam meningkatkan hasil belajar Matematika. Berdasarkan angket siswa, aspek pemberian bantuan dan motivasi belajar diperoleh hasil 83% atau sangat baik.